2016
DOI: 10.1007/s10266-016-0280-3
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue changes after a mandibular osteotomy for symmetric skeletal class III malocclusion

Abstract: The soft tissue profile is crucial to esthetics after orthognathic surgery. The aim of this study was to assess the soft tissue changes of the subnasal and submental regions more than 1 year after a sagittal split ramus osteotomy (SSRO) in patients with skeletal class III malocclusion. A total of 22 patients with mandibular prognathism were included in this study. Patients had lateral cephalograms before and more than 1 year after they underwent an isolated SSRO. Soft and hard tissue changes were assessed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…This tendency was similar to a previous study. 13 Thus, discussing this change with the patient should be important before surgery. However, this region was affected by the axis and position of the maxillary anterior teeth and may have been affected by postoperative orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tendency was similar to a previous study. 13 Thus, discussing this change with the patient should be important before surgery. However, this region was affected by the axis and position of the maxillary anterior teeth and may have been affected by postoperative orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The line wherein S-N rotated by 7 degrees with S as the fulcrum was referred to as the x axis, as previously described. 13 The perpendicular line to the x axis which go through S was referred to as the y axis, as previously described. 14 This x-y coordinate was used to assess the change in points.…”
Section: Cephalometric Analysismentioning
confidence: 99%
“…Modifications of the nasolabial angle determine the esthetic assessment of the area (van Loon et al, 2015). Ohba et al (2017), in a study of subjects with a class III facial deformity who underwent orthognathic surgery, found that a greater mandibular retrusion in the postoperative stage is associated with a greater nasolabial angle. For their part, Tiwari et al (2018), analyzing 3D photos obtained 12 months after orthognathic surgery, showed a relation between 1 mm of maxillary advancement with increase in average of 1.81º in the nasolabial angle and between 1 mm of maxillary regression related to a decrease of 2.73º in this angle.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Estimation of the change in soft tissue esthetics after orthog-nathic surgery is generally performed by lateral cephalograms, lateral photographs and 3-dimensional lateral images but patients generally evaluate themselves based on how they look in the mirror. 1,2,4 Frontal view, also called "social profile," affects the perception of social attractiveness more than the profile view. 1,3,5 The esthetics of the submental-cervical region can affect the perceived esthetics of the face in profile and frontal views therefore esthetics of this region should be evaluated both in isolation and together with other parts of the face.…”
mentioning
confidence: 99%
“…One of the purposes of orthodontic treatment and orthognathic surgery is to improve the soft tissue esthetics 1–3. Estimation of the change in soft tissue esthetics after orthognathic surgery is generally performed by lateral cephalograms, lateral photographs and 3-dimensional lateral images but patients generally evaluate themselves based on how they look in the mirror 1,2,4. Frontal view, also called “social profile,” affects the perception of social attractiveness more than the profile view 1,3,5…”
mentioning
confidence: 99%